Excretory Function of Intestinal Tract Enhanced in Kidney Impaired Rats Caused by Adenine - Yu Yun; Tao Gao; Yue Li; Zhiyi Gao; Jinlian Duan; Hua Yin; Weigang Duan (The Scientific World Journal)
The main aim of the study was to prove the compensative effect of intestine for renal function. Rat kidney was impaired by intragastrically administrating adenine (400 mg per day for 5 days). Intestinal tract was harvested and equally divided into 20 segments except cecum. Kidneys were harvested and histologically examined with hematoxylin-eosin staining kits. Uric acid, urea (BUN), and creatinine in serum were determined with assay kits, and BUN and creatinine in every intestinal segment were also determined. The results showed that adenine was able to increase uric acid level in serum from 20.98±6.98 μg/mL to 40.77±7.52 μg/mL and cause renal function damage with BUN (from 3.87±0.62 mM to 12.33±3.27 mM) and creatinine (from 51.48±6.98 μM to 118.25±28.63 μM) increasing in serum and with abnormally micromorphological changes in kidney. The amount of BUN and creatinine distributed in intestinal tract was positively correlated with those in blood. In impaired renal function rats, the amount of BUN (from 4.26±0.21 μMole to 10.72±0.55 μMole) and creatinine (from 681.4±23.3 nMole to 928.7±21.3 nMole) distributed in intestinal tract significantly increased. All the results proved that intestinal tract had excretory function compensative for renal function.